THE DEATH PENALTY AS DETERRENT PUNISHMENT: A REVIEW OF EFFECTIVENESS OF DEATH PENALTY IN BANGLADESH - Erfan, Abdullah Mohammad; Islam, Mohammad Saiful; Malek, Abdul (Diponegoro Law Review, 2025)
Punishment is a crucial tool for crime prevention and deterrence. Among other punishments, the death penalty is the harshest punishment in Bangladesh. In the past, many have believed that the death penalty effectively deters crime. However, there remains debate over whether the death sentence actually works to prevent crime. Bangladesh encompasses a broad spectrum of offenses, including both serious crimes and nonviolent offenses, that are subject to the death penalty, and the country aims to expand the list of offenses punishable by this sentence. However, the effectiveness of the death penalty in deterring crimes is questionable. The most important resources for a State are its human resources. The death penalty, however, annihilates the right to life and dashes all of humanity's hopes and aspirations. Protecting their lives is crucial because of this. The study aims to examine and assess the current regulations of the death sentence in preventing crime. Subsequently, the study attempts to demonstrate how effectively the death penalty closes gaps in the justice system and deters crime. To conclude the study, it has been undertaken in doctrinal legal research with analytical approaches. The first part of this study looks at the offenses from numerous actions that might result in the death penalty. Second, statistics indicate that even when the death sentence is still in place, crime does not greatly decline. Finally, it recommends substitute punishments that can be carried out rather than the death penalty.